Expression of Platelet Derived Growth Factor a, Its Receptor, and Integrin Subunit Alpha V in Feline Injection-Site Sarcomas - Ahmed Ishtiaq (Sciendo, 2021)
Injection-site sarcomas are considered an important entity in veterinary oncology, especially in cats. The current study investigated the immunohistochemical expression of platelet-derived growth factor A (PDGFA), platelet-derived growth factor receptor-α (PDGFR-α), and integrin alpha subunit v in feline injection-site sarcomas (FISS). A total of 14 paraffin-embedded tissue samples previously diagnosed as soft tissue sarcomas were selected from the departmental archive and sectioned at 5µm using a microtome. Tissue sections were stained with Hematoxylin & Eosin, Alcian blue-Periodic Acid Schiff (AB-PAS), Masson’s Trichrome, and immunohistochemically for PDGFA, PDGR-α, and integrin alpha v. The majority of the tumors were fibrosarcomas (n=13/14), except one case of myxoid liposarcoma. The tumors occurred at sites commonly used for injections or vaccine administration. Histologically, tumors were characterized by peripheral infiltration of mononuclear cells mainly lymphocytes, variable sized central necrotic areas, and many multinucleated tumor giant cells. AB-PAS staining revealed the presence of myxoid or mucinous areas in (8/14) tumors while trichrome staining demonstrated a variable amount of collagenous stroma in 12/14 tumors. Vimentin immunoreactivity was observed in all the tumors while smooth muscle actin and muscle actin staining was noticed in four and two cases, respectively. PDGFA and PDGFR-α immunoexpression was observed in all 14 cases while integrin alpha v in 13/14 cases. The results of the current study indicate that fibrosarcoma is the major morphologic phenotype of FISS. The PDGFA, its receptor, and integrin alpha v immunoexpression are increased in these tumors in cats which elucidates their role in the pathogenesis of FISS.